Biomass allocation and resource use strategies of shrubs and dwarf shrubs in Southern Patagonia: implications for developing a natural capital accounting framework - Peri, Pablo Luis; Lasagno, Romina Gisele; Ladd, Brenton (Elsevier, 2025)
In situ measurements were made to gain insight into resource use strategies of the perennial flora of cold arid steppe in Southern Patagonia. We measured biomass allocation and nutrient concentration in 3 tall shrub and 3 dwarf-shrub species corresponding to two sizes (small and large plants). Total biomass of individual plants was mainly determined by functional group and species and ranged from 45 for small Nassauvia ulicina to 9630 g dry matter plant− 1 for large Mulguraea tridens shrubs. Specific Leaf Area in tall shrubs (6.5 m2 kg− 1 DM) was lower than in dwarf shrubs (10.7 m2 kg− 1 DM). Leaf nutrient concentrations and reabsorption were variable in terms of correlation to SLA. There was a tendency for the tall shrubs to allocate a relatively high percentage of biomass to the leaf mass fraction. The perennials of the steppe in southern Patagonia have evolved a diverse range of functional traits to adapt to adversity. Based on this admittedly small sample we conclude that tall shrubs have evolved a stress tolerance strategy whereas dwarf shrubs have evolved an acquisitive/avoidance strategy in response to the same selection pressures. We briefly discuss how such baseline information could be integrated into a natural capital accounting framework.